Dirasah Sikulujiyah Adabiyah Sigmund Freud Fi Syakhshiyah “Samiyah” Fi Masrahiyah Qitath wa Firan Li Ali Ahmad Bakatsir - M Romadhoni (Arabic Language and Letters Department, 2020)
This study aims to determine the form and causes of the characterization of the character